Evaluation of known and novel inhibitors of Orai1-mediated store operated Ca2+ entry in MDA-MB-231 breast cancer cells using a Fluorescence Imaging Plate Reader assay. Issue 1 (1st January 2017) - Azimi, Iman; Flanagan, Jack U.; Stevenson, Ralph J.; Inserra, Marco; Vetter, Irina; Monteith, Gregory R.; Denny, William A.
Graphical abstract: Highlights: A Fluorescence Imaging Plate Reader assay for calcium channel inhibitors. Inhibitors of the Orai1 SOCE Ca 2+ channel that do not affect Ca 2+ store release. Similarity-based screening assay to identify triazole-based Orai1 inhibitors. Abstract: The Orai1 Ca 2+ permeable ion channel is an important component of store operated Ca 2+ entry (SOCE) in cells. It's over-expression in basal molecular subtype breast cancers has been linked with poor prognosis, making it a potential target for drug development. We pharmacologically characterised a number of reported inhibitors of SOCE in MDA-MB-231 breast cancer cells using a convenient Fluorescence Imaging Plate Reader (FLIPR) assay, and show that the rank order of their potencies in this assay is the same as those reported in a wide range of published assays. The assay was also used in a screening project seeking novel inhibitors. Following a broad literature survey of classes of calcium channel inhibitors we used simplified ligand structures to query the ZINC on-line database, and following two iterations of refinement selected a novel Orai1-selective dichlorophenyltriazole hit compound. Analogues of this were synthesized and evaluated in the FLIPR assay to develop structure–activity relationships (SAR) for the three domains of the hit; triazole (head), dichlorophenyl (body) and substituted phenyl (tail). For this series, the results suggested the need for a lipophilic tail domain and an out-of-plane twist between the body and tail domains.